Outcome of cases of Mitral Stenosis after Percutenuous Transvenous Mitral Commissurotomy (PTMC) - Ahasan, Syed Ali; Hasan, ATM Iqbal; Hasan, ATM Iqbal; Maruffuzaman, SK; Bari, MA (Nepalese Heart Journal, 2004)
This prospective study was carried out in the National Institute of Cardiovascular Diseases and Hospital (NIC VD), Dhaka, Bangladesh during the period January 2002 to December 2002. The result of percutenuous ballon mitral valvotomy were evaluated in 153 cases of mitral stenosis patients (mean age 36±15 years) with symptomatic rheumatic mitral stenosis with single Inoue ballon technique PTMC results significant increase mitral valve area. 79.18 to 1.86 ±.37. Transmitral mean pressure gradient 19.6 ± 8.9 to 3.7±38, Decrease mean left atrial size 41.33±9.3 to 30.56±8.16 and Pulmonary artery systolic pressure 56±24 to 39 ±17, Peak pressure gradient (PPG) 19.6±8.9 to 8.7 ±3.8, But lower incidence of mitral regurgitation, only two cases developed MR grade Ill which were treated medically, one patient develop moderate haemopericardium which was treated conservatively. One patient was failed due to severe tight MS of valve area 0.5. No surgical intervention was needed.